Past in the making : historical revisionism in Central Europe after 1989 - Kopeček, Michal (Central European University Press, 2008)
Historical revisionism, far from being restricted to small groups of 'negationists, ' has galvanized debates in the realm of recent history. The studies in this book range from general accounts of the background of recent historical revisionism to focused analyses of particular debates or social-cultural phenomena in individual Central European countries, from Germany to Ukraine and Estonia. Where is the borderline between legitimate re-examination of historical interpretations and attempts to rewrite history in a politically motivated way that downgrades or denies essential historical facts? How do the traditional 'national historical narratives' react to the 'spill-over' of international and political controversies into their 'sphere of influence'? Technological progress, along with the overall social and cultural decentralization shatters the old hierarchies of academic historical knowledge under the banner of culture of memory, and breeds an unequalled democratization in historical representation. This book offers a unique approach based on the provocative and instigating intersection of scholarly research, its political appropriations, and social reflection from a representative sample of Central and East European countries.